2006
DOI: 10.2174/092986606777841271
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Thermal Characterization of a Novel Peroxidase from a Local Chick Pea Cultivar

Abstract: A novel peroxidase isolated from a local chick pea (Cicer arietinum L.) cultivar (Balksar 2000) was purified by means of ammonium sulfate precipitation, DEAE-cellulose chromatography and two runs on gel filtration. The purified enzyme has a specific activity of 2045 U/mg with 17 % activity recovery. The molecular mass of the enzyme was estimated to be 39 kDa by SDS-polyacrylamide gel electrophoresis. Optimum pH and temperature of the enzyme were 5.5 and 45 degrees C respectively. The thermal denaturation of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…Various studies have shown that peroxidase activity is susceptible to modulation by certain metal ions (Marzouki et al 2005;Bhatti et al 2006). The mixed type inhibition pattern obtained for each of the inhibitors indicates that they are able to inhibit E. crassipes leaf peroxidase by binding to either the free enzyme or its enzyme-substrate complex.…”
Section: Properties Of Purified Eichhornia Crassipes Leaf Peroxidasementioning
confidence: 94%
See 1 more Smart Citation
“…Various studies have shown that peroxidase activity is susceptible to modulation by certain metal ions (Marzouki et al 2005;Bhatti et al 2006). The mixed type inhibition pattern obtained for each of the inhibitors indicates that they are able to inhibit E. crassipes leaf peroxidase by binding to either the free enzyme or its enzyme-substrate complex.…”
Section: Properties Of Purified Eichhornia Crassipes Leaf Peroxidasementioning
confidence: 94%
“…Other studies have shown peroxidase activity to have a similar optimum temperature range. Bhatti et al (2006) showed that activity of peroxidase from lettuce stem had an optimum temperature of 45 °C, while activity of peroxidase from cauliflower had optimum temperature of 30 °C (Koksal, Gulcin 2008).…”
Section: Properties Of Purified Eichhornia Crassipes Leaf Peroxidasementioning
confidence: 99%
“…Similarly, peroxidase from peels of Citrus reticulata var. showed maximum activity at pH 6.0 [44] and the peroxidase from a local chick pea cultivar showed maximum activity at pH 5.5 [45].…”
Section: Effect Of Phmentioning
confidence: 99%
“…The peroxidase from a local chick pea cultivar showed maximum activity at 45°C [45]. Red cabbage (B. oleracea) showed a maximum activity at 30°C [47].…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…[31] For example, molecular weight of POD was 44 kDa for cauliflower, [18] 38 kDa for artichoke, [32] 50 kDa for windmill palm tree, and 39 kDa for chickpea cultivar. [33] POD could be monomer such as found in Chlorella vulgaris or homotetramer such as found in oil from palm leaf. [34] Characterization studies Optimum pH and pH stability pH is crucial since it determines the ionization state of amino acid side chain on the enzyme and substrate.…”
Section: Molecular Weight and Puritymentioning
confidence: 99%